Three Novel KIT Polymorphisms Found in Horses with White Coat Color Phenotypes - Nikol A. Obradovic; Aiden McFadden; Katie Martin; Micaela Vierra; Kaitlyn McLoone; Erik Martin; Adelaide Thomas; Robin E. Everts; Samantha A. Brooks; Christa Lafayette (Animals)
This paper reports three novel KIT variants likely responsible for previously unexplained white patterning phenotypes observed in three groups of horses. White spots and markings may have substantial consequences on the value and health of domesticated horses. This study aims to elucidate the genetic mechanisms underlying depigmented coat colors to aid in producing prosperous herds. Aligned whole genome sequences were manually screened to identify three polymorphisms in a family of Anglo-Arabian horses (N = 7), a family of Warmblood horses (N = 5), and a single stock-type mare with unexplained white markings. Sanger sequencing confirmed the presence of the variants, and in silico predictive programs were used to predict the functional impacts of each. We propose to term the novel variants W37, W38, and W39, respectively, per convention. The W37 polymorphism was always observed in the presence of one W35 allele, suggesting complete linkage. All three variants were predicted to alter or remove the KIT protein active domain, repressing typical protein folding and impacting pathways that upregulate pigmentation. The severe predicted impact on biological function suggests that these variants may cause increased white spotting, providing a possible explanation for the depigmentation phenotypes observed in affected individuals.